An evaluation of the tumour endothelial marker CLEC14A as a therapeutic target in solid tumours. (21st July 2020) - Robinson, Joseph; Whitworth, Katharine; Jinks, Elizabeth; Nagy, Zsuzsanna; Bicknell, Roy; Lee, Steven P
Abstract: Earlier studies identified the transmembrane cell surface C‐type lectin CLEC14A as a putative tumour endothelial marker. For CLEC14A to progress as a vascular target in solid tumours an in‐depth analysis of CLEC14A expression in human healthy and tumour tissue is needed. It is here shown that an analysis of 5332 RNA expression profiles in the public domain confirmed high expression of CLEC14A in tumour compared to healthy human tissue. It is further shown by immunohistochemistry that CLEC14A protein is absent, or expressed at a very low level, in healthy human and primate tissue. In contrast, CLEC14A is expressed on the vasculature of a range of human solid tumours, with particularly high expression in more than half of renal cell carcinomas. Elevated levels of CLEC14A transcripts were identified in some non‐cancer pathologies; such comorbidities may need to be excluded from trials of therapies targeting this marker. It is further shown that, as CLEC14A expression can be induced by the absence of shear stress, it is imperative that freshly collected as opposed to aged or post‐mortem tissue be analysed. We conclude that CLEC14A is a promising target to enable development of novel anti‐cancer therapies for solid tumours.